Exploring Primary Preservice Teachers’ Agency and Systems Thinking in the Context of the COVID-19 Pandemic - Uskola, Araitz; Puig, Blanca (Frontiers in Education, 2022)
The science education curriculum has become increasingly focused on the study of complex systems and on the development of agency so that students make decisions on relevant issues. The current pandemic has underlined the need to look at health from a systemic “One Health” approach, but little is known about the knowledge, skills, attitudes, and actions necessary for individuals to successfully contribute to One Health.This study seeks to contribute to this knowledge, and explores preservice elementary teachers’ (PETs´) agency and systems thinking competencies to propose actions for preventing future pandemics from the One Health approach. The participants were 47 preservice elementary teachers (PETs) working on a set of activities about the COVID-19 pandemic, in which they were asked about ways to prevent future pandemics. Content analysis of individual written responses was applied for addressing the level of systems thinking and the sense of personal and collective responsibility towards the action proposed. Results show that PETs initially referred mainly to actions in the human health dimension, and that the systems thinking showed a higher level when they made the activity in groups after reading information. Collectively proposed actions showed a lack of agency or individual responsibility compared to individually proposed ones. The implications of the results for science teaching are discussed.